Nigerian Economic Development, Fiscal Federalism, and Contending Issues: Theoretical and Practical Approaches to Methodology - Sulaiman Taiwo Hassan; Abalaka J.N; Ajiteru S.A.R (Global Economics: International Journal of Economic, Social and Development Sciences, 2025)
This essay looks at an investigation into the economies, A significant topic in the policy equation of many has been fiscal federalism, which reflects the degree of fiscal autonomy and responsibility granted to subnational government developing, transitional, and industrialized nations. Scholarly attention has been drawn to Nigeria's federalism because of its intricacy and vibrancy. This is due to the fact that it has created numerous issues that could jeopardize the Nigerian state's corporate existence and continuity. Therefore, the relationship between Nigeria's fiscal federalism and the oil-rich nation's lack of economic development is highlighted in this study. Our main contention is that Nigeria's fiscal federalism has not sparked the growth that the system's designers had hoped for. Therefore, this essay looked at Nigeria's fiscal federalism's development, composition, and practices. In order to do this, the study used secondary sources to collect data and combined descriptive and analytical methodologies. According to the report, Nigeria has not functioned as a a federal constitution, making it a true federation. Taxing authority and fiscal responsibility are still heavily concentrated. Numerous issues, such as the federal government's dominance in income sharing, the lengthy period of military interregnum rule, and an excessive reliance on Federation Account revenue, have hindered Nigeria's practice of fiscal federalism. This study investigated how fiscal federalism and the chosen distribution formula contribute to unhappiness and violent agitation. In order to do this, the study used secondary sources to collect data and combined descriptive and analytical methodologies. Therefore, the study came to the conclusion that in order to promote sound fiscal independence, the federal government should give state governments some of its taxing authority. and rivalry between states.